Increased IL‐21 expression in chronic rhinosinusitis with nasalpolyps. Issue 2 (February 2015) - Xiao, L.; Wei, Y.; Zhang, Y.‐N.; Luo, X.; Yang, B.‐Y.; Yu, S.‐F.; Wu, X.‐M.; Wu, C.‐Y.; Li, H.‐B.
Summary Background IL‐21 is a key cytokine for regulating B cell immunity, which is involved in several inflammatory conditions. This study sought to define a role for IL‐21 in activated B lymphocytes and enhanced tissue eosinophilia in NP tissues during the pathogenesis of chronic rhinosinusitis with nasal polyps (CRSwNP). Methods NP and uncinate process tissues were collected from 64 CRSwNP patients, 25 CRSsNP patients, and 29 control subjects. IL‐21 expression was examined using IHC staining, qRT‐PCR, flow cytometry, and ELISA, and its clinical implication was evaluated. Moreover, the effects of IL‐21 on B cell differentiation and Ig production in cultured NP cells were examined in vitro. Results The mRNA and protein levels of IL‐21 were significantly increased in polyp tissues compared with control tissues (P < 0.05). Polyp IL‐21 level was significantly associated with polyp size, tissue eosinophilia and asthma comorbidity, and recurrence after surgery (P < 0.05). Both Th1 and Th17 cells were the main cellular sources of IL‐21 in polyp tissues. The percentage of IL‐21+CD4+ cells was significantly higher in polyp tissues compared with control tissues and matched PBMCs (P < 0.01). Accordingly, the percentage of CD19+CD20+/− CD38high cells was significantly higher in polyp tissues compared with control tissues (P < 0.01). Moreover, recombinant IL‐21 significantly increased the percentage of CD19+CD20+/− CD38high cells (plasmablasts) and IgG and IgA production in cultured NP cells in vitro (P < 0.05). Conclusion and Clinical Relevance Increased IL‐21 level in polyp tissues was associated with disease severity, local B cell activation, and immunoglobulin production, suggesting that IL‐21 might play an important role in promoting persistent mucosal inflammation in CRSwNP patients.